Long‐term outcomes with first‐ vs. second‐generation drug‐eluting stents in saphenous vein graft lesions. Issue 1 (29th May 2015) - Pokala, Nagendra R.; Menon, Rohan V.; Patel, Siddharth M.; Christopoulos, George; Christakopoulos, Georgios E.; Kotsia, Anna P.; Rangan, Bavana V.; Roesle, Michele; Abdullah, Shuaib; Grodin, Jerrold; Kumbhani, Dharam J.; Hastings, Jeffrey; et al.
Abstract : Background: As compared with bare metal stents, first‐generation drug‐eluting stents (DES) improved post‐procedural outcomes in aortocoronary saphenous vein graft (SVG) lesions, but there is limited information on outcomes after use of second‐generation DES in SVGs. Methods: We compared the outcomes of patients who received first‐ ( n = 81) with those who received second‐generation ( n = 166) DES in SVG lesions at our institution between 2006 and 2013. Major adverse cardiac events (MACE) were defined as the composite of all‐cause death, myocardial infarction, and target vessel revascularization. Results: Mean age was 66.0 ± 8.1 years and 97.6% of the patients were men. Mean SVG age was 11.1 ± 0.4 years. First‐generation DES were sirolimus‐eluting ( n = 17) and paclitaxel‐eluting ( n = 64) stents. Second‐generation DES were everolimus‐eluting ( n = 115) and zotarolimus‐eluting ( n = 51) stents. Median follow‐up was 41 months. At 2‐years post‐procedure, patients with first‐ and second‐generation DES had similar rates of death (20.91% vs. 20.27%, P = 0.916), target lesion revascularization (16.39% vs. 20.00%, P = 0.572), target vessel revascularization (20.97% vs. 23.16%, P = 0.747), myocardial infarction (26.15% vs. 23.00%, P = 0.644), and MACE (43.5% vs. 40.87%, P = 0.707), respectively. Conclusions: Outcomes with first‐ and second‐generation DES in SVGs are similar. Novel stent designs are needed to further improve the clinical outcomes in this challenging patient and lesion subgroup. © 2015 Wiley Periodicals, Inc.